Corrosion-resistant alloy cast-iron cylinder liner and method for manufacturing the same

CN123005218APending Publication Date: 2026-10-30江苏华晨气缸套股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611336274.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-12-16
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明的合金铸铁气缸套的基体为索氏体加细小片状石墨,其组织稳定;同时由于碳化物在基体组织中弥散均匀分布、极大提高了合金铸铁气缸套的耐腐蚀能力,且该合金铸铁气缸套因为碳硅当量低,减少了铸铁气缸套的石墨数量,铸铁中的铬高于正常气缸套铸件0.2-0.4%的含量,达到0.6-0.8%,特别是加入0.7-0.9%的锡,这两种元素固溶于基休中,产生锡铬合金,该合金为基体内部主要组成成分,该合金材料具有良好的抗腐蚀能力。外部的铬(Cr)原子与氧(O),形成Cr2O3保护膜,使铸件材料在酸性条件下不断释放Cr2O3,起到防腐作用。因此该铸铁气缸套不仅有高的抗腐蚀性,并且具有良好的强度、硬度,可大大提高发动机气缸套的使用寿命。尤其对使用甲醇、乙醇、甲烷等燃料的发动机气缸套时,抗腐蚀作用更显著。(没有抗腐蚀能力或者抗腐蚀能力较弱的普通气缸套大约会在连续工作2000h-3000h,之后会产生点蚀、应力腐蚀开裂的腐蚀现象,经实验Cr2O3保护膜在甲醇、乙醇、甲烷等新能源燃料工作情况下,能够保证6000h不会产生点蚀、应力腐蚀开裂的腐蚀现象,由于气缸套Cr2O3保护膜较薄、气缸套在工作过程中会产生轻微磨损。大部分Cr2O3保护膜会在5500h时,损耗完全。锡铬合金有良好的抗腐蚀性能,可以在Cr2O3保护膜,完全损耗后,在甲醇燃料环境下保证9000h不会产生点蚀、应力腐蚀开裂的腐蚀现象。乙醇燃料环境下保证9500h不会产生点蚀、应力腐蚀开裂的腐蚀现象。甲烷燃料环境下保证10000h不会产生点蚀应力腐蚀开裂的腐蚀现象。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to an anti-corrosion alloy cast iron cylinder liner and a preparation method thereof. Specifically, after smelting according to a proportion, molten iron A is obtained, and then a tempering treatment is carried out to obtain molten iron B; the molten iron B is poured through centrifugal casting to obtain an alloy cast iron piece; the centrifugal casting smelting temperature is controlled to be 1520-1550 DEG C, the pouring temperature is controlled to be 1350-1390 DEG C, the centrifugal casting ejection temperature is controlled to be 700-800 DEG C, and after ejection, air cooling is carried out; after the cast piece reaches normal temperature after about 8 hours, the alloy cast iron cylinder liner is obtained. The produced alloy cast iron cylinder liner has good strength and hardness, and in particular has strong corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of corrosion resistance technology for alloy cast iron cylinder liners, specifically to a corrosion-resistant alloy cast iron cylinder liner and its preparation method. Background Technology

[0002] The cylinder liner is a core component of the engine. It is installed inside the engine and together with the piston and cylinder head, it forms the combustion chamber and the working space for piston movement. When the engine is working, the cylinder liner is subjected to high pressure, high temperature, piston ring friction, component impact, and environmental influences such as water, vapor, and acid corrosion.

[0003] In recent years, with increasing demands from users for various performance indicators of cylinder liners, as well as requirements for low pollution and low emissions, users not only require continuous upgrades in the material quality of cylinder liners, but also constantly seek new, inexpensive, and environmentally friendly fuels to replace traditional fuels. This necessitates cylinder liners with good strength and hardness, as well as good corrosion resistance when using alternative fuels such as methanol, ethanol, methane, and hydrogen. Given the unique working environment of cylinder liners, which withstand high pressure, high temperature, friction, impact, and corrosion from water, vapor, and acids, corrosion resistance is one of the most important core parameters of cylinder liners. Therefore, the design, fabrication, and application of corrosion-resistant cylinder liner casting materials are essential. Summary of the Invention

[0004] This invention provides a corrosion-resistant alloy cast iron cylinder liner and its preparation method. The produced alloy cast iron cylinder liner has good strength and hardness, and in particular, strong corrosion resistance.

[0005] The technical solution adopted in this invention is: A method for preparing a corrosion-resistant alloy cast iron cylinder liner includes the following steps: Smelting: Add No. 18 pig iron, scrap steel, and carbon recarburizer with 98% carbon content to a 3t medium-frequency electric furnace for smelting, including 1500Kg of pig iron, 1350Kg of scrap steel, and 45Kg of carbon recarburizer; The pig iron is added in three batches of 500+500+500 kg; the scrap steel is added in three batches of 450+450+450 kg; the carbon raiser is added in a single batch of 45 kg. The feeding process is continuous in batches, with the smelting power controlled at 80% of the total power. When the materials in the furnace are completely melted and the molten iron surface is visible at the furnace opening, the power is increased to 100%. At 100% power, the molten iron boils at a high temperature for 5-10 minutes. A slag remover is added to the surface of the molten iron for slag removal until the surface is clean. The smelting temperature is 1520-1550℃ to obtain molten iron A. Tempering: Add ferrosilicon (75%), ferromanganese (65%), ferrophosphorus (24%), ferrochrome (60%), copper (99%), and tin (99%) to molten iron A for tempering. The required weight of the alloy is calculated based on the difference between the original molten iron A and the target value B. After adding the alloy, molten iron B is finally obtained by spectral detection. After adding the alloy, melt at a temperature of 1520-1550℃ for 5-10 minutes. Inoculation: Molten iron B is inoculated with a silicon-strontium inoculant to obtain a composition of 2.5-3.1 wt% C, 1.4-2.5 wt% Si, 0.5-1.2 wt% Mn, 0.1-0.4 wt% P, 0.02-0.12 wt% S, 0.3-1.5 wt% Cr, 0.5-1.5 wt% Cu, 0.6-1.0 wt% Sn, with the balance being Fe; The molten iron after inoculation is poured through centrifugal casting, and after being removed from the mold, it is air-cooled to obtain alloy cast iron cylinder liners.

[0006] Based on the above scheme, as a preferred option, the following composition is obtained: 3.0~3.1wt% C, 1.9~2.1wt% Si, 0.75~0.85wt% Mn, 0.2~0.3wt% P, 0.04~0.06wt% S, 0.6~0.8wt% Cr, 0.6~0.7wt% Cu, 0.7~0.9wt% Sn, with the balance being Fe.

[0007] Based on the above scheme, as a preferred option, the pouring temperature of the centrifugal casting is controlled at 1350~1390℃ and the unmolding temperature is 700-800℃.

[0008] Based on the above scheme, as a preferred method, the cooling method is to air cool with the metal mold for 30 seconds, then water cool with the metal mold for 240 seconds, then air cool with the metal mold for 120 seconds, until the blank cavity reaches 700-800℃, then remove it from the mold and air cool to the natural temperature.

[0009] In this invention, the carbon (C) content is 2.5~3.1 wt%, and the silicon (Si) content is 1.4~2.5 wt%. In normal alloy cast iron cylinder liners, the lower the C content, the finer the graphite flakes in the matrix, resulting in higher strength and stronger corrosion resistance. However, the probability of white cast iron is greater. Higher Si content increases heat resistance, but reduces the strength and wear resistance of the cast cylinder liner. Therefore, it is necessary to comprehensively consider and test the combined effects of carbon and silicon content on cylinder liner performance. Only within the above ranges can the corrosion resistance, strength, and hardness of the alloy cast iron cylinder liner be guaranteed. In specific experiments, the C content is 3.0~3.1%, more specifically, 3.01%, 3.03%, 3.07%, and 3.09%. In specific implementations, the Si content is 1.9~2.1%, more specifically, 1.92%, 1.97%, 2.05%, and 2.08%.

[0010] The addition of manganese (Mn) is primarily to reduce the oxygen content of molten iron, improve its purity, and eliminate its hot brittleness, thereby enhancing its hot workability and increasing the strength of castings. However, excessive Mn content can lead to fatal defects such as shrinkage cavities and porosity. Considering all factors, an Mn content of 0.5% to 1.2% is suitable. In specific experimental implementations, an Mn content of 0.75% to 0.85% is optimal. More specifically, the Mn content is 0.77%, 0.79%, 0.82%, and 0.84%.

[0011] The addition of phosphorus (P) is primarily to form a certain amount of phosphorus eutectic, thereby improving the hardness and wear resistance of the cast cylinder liner. Simultaneously, the addition of phosphorus improves machinability. The hard phase generated by the phosphorus eutectic enhances its corrosion resistance. However, excessive P content can lead to a loss of ductility and a decrease in strength in the casting. Therefore, the P content must be controlled within a specific range. A P content of 0.1% to 0.4% is suitable. In specific experimental implementations, an optimal P content of 0.2% to 0.3% is achieved. More specifically, the P content is 0.21%, 0.24%, 0.26%, and 0.29%.

[0012] The main purpose of adding sulfur (S) is to lower the overall melting point of the casting, refine the metallographic structure, and increase the casting's plasticity. However, excessive S content can lead to a decrease in the mechanical properties and corrosion resistance of the casting; therefore, the S content must be controlled within a specific range. An S content of 0.02-0.12% is suitable. In specific experimental implementations, an S content of 0.04-0.06% is optimal. More specifically, the S content is 0.045%, 0.050%, 0.053%, and 0.057%.

[0013] The addition of Cu is primarily to refine the matrix structure, improve the strength and hardness of cast iron cylinder liners, and enhance their oxidation resistance. Cu improves the rapid fusion of tin-chromium alloys, ensuring their stability. It also further enhances the corrosion resistance of tin-chromium alloys. Excessive copper content can lead to a decrease in the hardness of castings and increased wear. Therefore, the Cu content must be controlled within a specific range, with 0.5-1.5% being suitable. In specific experimental implementations, a Cu content of 0.6-0.7% is optimal. More specifically, the Cu content is 0.62%, 0.64%, 0.67%, and 0.69%.

[0014] The addition of Cr (Cr) is primarily to improve the hardenability, strength, and hardness of castings, especially enhancing their corrosion resistance and significantly improving their resistance to oxidation, acids, alkalis, and atmospheric corrosion. However, high Cr content can lead to increased brittleness and machinability. Therefore, the Cr content must be controlled within the range of optimal overall performance. Specific experiments have shown that when the Cr content is less than 0.3%, a Cr₂O₃ protective film cannot be formed. When the Cr content is greater than 1.5%, the hardness reaches 45-50 HRC, making machining difficult, and simultaneously reducing the casting's corrosion resistance. Therefore, a Cr content of 0.3-1.5% is suitable. In specific experiments, an optimal Cr content of 0.6-0.8% was found. More specifically, the Cr content is 0.63%, 0.68%, 0.72%, and 0.76%.

[0015] The addition of Sn is primarily to improve the hardness, strength, and especially corrosion resistance of castings. Specific experiments revealed that the corrosion resistance of castings decreased linearly with decreasing tin content (0.6% → 0.5% → 0.4% → 0.3% → 0.2% → 0.1%). When the tin content exceeded 1.0%, the metallographic structure of the casting began to tend towards white iron formation, resulting in extremely poor machinability. Furthermore, high Sn content significantly increased casting costs. Therefore, the Sn content must be appropriately controlled. A Sn content of 0.6-1.0% is suitable. In specific experiments, an optimal Sn content of 0.7-0.9% was achieved. More specifically, Sn contents of 0.71%, 0.79%, 0.83%, and 0.88% were observed. According to experiments, when the Cr content in the casting is 0.6-0.8% and the Sn content is 0.7-0.9%, the tin-chromium alloy is stable, the casting achieves optimal corrosion resistance, and the machinability is excellent.

[0016] The present invention has the following technical effects: The alloy cast iron cylinder liner of this invention has a matrix of sorbite with fine flake graphite, resulting in a stable structure. Simultaneously, the uniform dispersion of carbides within the matrix significantly enhances the corrosion resistance of the alloy cast iron cylinder liner. Furthermore, the low carbon-silicon equivalent of this alloy cast iron cylinder liner reduces the amount of graphite, and the chromium content in the cast iron is 0.6-0.8%, higher than the 0.2-0.4% found in normal cylinder liner castings. In particular, the addition of 0.7-0.9% tin, with these two elements dissolved in the matrix, forms a tin-chromium alloy, which is the main component of the matrix and exhibits excellent corrosion resistance. External chromium (Cr) atoms react with oxygen (O) to form a Cr2O3 protective film, allowing the casting material to continuously release Cr2O3 under acidic conditions, thus providing corrosion protection. Therefore, this cast iron cylinder liner not only has high corrosion resistance but also good strength and hardness, significantly extending the service life of engine cylinder liners. The corrosion resistance is particularly significant for cylinder liners used in engines employing fuels such as methanol, ethanol, and methane. Ordinary cylinder liners with little or no corrosion resistance typically develop pitting and stress corrosion cracking after approximately 2000-3000 hours of continuous operation. Experiments show that the Cr2O3 protective film can guarantee against pitting and stress corrosion cracking for 6000 hours under conditions using new energy fuels such as methanol, ethanol, and methane. However, due to the thinness of the Cr2O3 protective film on the cylinder liner and the slight wear that occurs during operation, most of the Cr2O3 protective film is completely worn away by 5500 hours. Tin-chromium alloys, with their excellent corrosion resistance, can guarantee against pitting and stress corrosion cracking for 9000 hours under methanol fuel conditions, 9500 hours under ethanol fuel conditions, and 10000 hours under methane fuel conditions. Detailed Implementation

[0017] To further understand the present invention, the following detailed description, in conjunction with embodiments, is provided. However, this is not intended to limit the scope of the invention. It should be understood that these descriptions are merely for further illustrating the features and advantages of the invention, and not for limiting the scope of the claims. Any equivalent substitutions made in the art based on the disclosure of this invention are within the protection scope of this invention.

[0018] A method for preparing an alloy cast iron cylinder liner includes the following steps: The composition is as follows: C: 2.5~3.1wt%, Si: 1.4~2.5wt%, Mn: 0.5~1.2wt%, P: 0.1~0.4wt%, S: 0.02~0.12wt%, Cr: 0.3~1.5wt%, Cu: 0.5~1.5wt%, Sn: 0.6~1.0wt%, with the balance being Fe. After smelting according to the specified proportions, a tempering and quenching treatment (inoculation treatment) is performed to obtain molten iron B. The molten iron is then centrifugally cast to obtain alloy cast iron parts.

[0019] The centrifugal casting melting temperature is controlled at 1520-1550℃, the pouring temperature is controlled at 1350-1390℃, and the centrifugal casting unmolding temperature is controlled at 700-800℃. After unmolding, the casting is air-cooled, and after about 8 hours when the casting reaches room temperature, various performance tests are performed.

[0020] This invention provides an optimal method for preparing alloy cast iron cylinder liners, comprising the following steps: The composition is as follows: C: 3.0~3.1wt%, Si: 1.9~2.1wt%, Mn: 0.75~0.85wt%, P: 0.2~0.3wt%, S: 0.04~0.06wt%, Cr: 0.6~0.8wt%, Cu: 0.6~0.7wt%, Sn: 0.7~0.9wt%, with the balance being Fe. This invention significantly improves the strength and hardness of alloy cast iron cylinder liners by optimizing material composition design and controlling manufacturing processes. In particular, its corrosion resistance is greatly enhanced. Its tensile strength can reach over 300MPa, and its hardness can reach 250-310HB. Under a constant temperature environment of 40℃, its corrosion loss rate is 0.315%, and its corrosion resistance is improved by 94.4%.

[0021] Examples 1-20 To further understand this invention, it will be comprehensively described from the perspective of some experimental implementation cases. The experimental method is the controlled variable method, and the specific operation is as follows: Smelting: Add No. 18 pig iron, scrap steel, and carbon recarburizer with 98% carbon content to a 3t medium-frequency electric furnace for smelting, including 1500Kg of pig iron, 1350Kg of scrap steel, and 45Kg of carbon recarburizer; The pig iron is added in three batches of 500, 500, and 500 kg, and the scrap steel is added in three batches of 450, 450, and 450 kg. The carburizing agent is added in a single batch of 45 kg. The feeding process is continuous in batches. During this process, the smelting power is controlled at 80% of the total power. When the materials in the furnace are completely melted and the molten iron surface is visible at the furnace opening, the power is increased to 100%. At 100% power, the molten iron boils at a high temperature for 5-10 minutes. A slag remover is added to the surface of the molten iron for slag removal until the surface is clean. The smelting temperature is 1520-1550℃ to obtain molten iron A. Tempering: A C, Si, Mn, P, Cu, Cr, and Sn alloy is added to molten iron A for tempering. The required weight of the alloy is calculated based on the difference between the original molten iron A and the target molten iron B. The proportions of C, Si, Mn, P, and Cu remain constant in each experiment, while the contents of Cr and Sn vary. Specifically: C: 3.0 wt%, Si: 2.0 wt%, Mn: 0.8 wt%, P: 0.25 wt%, S: 0.05 wt%, Cu: 0.7 wt%, Cr: 0.3~1.5 wt%, Sn: 0.6~1.0 wt%, with the balance being Fe. After adding the alloy, spectral analysis is used to obtain molten iron B. The molten iron B is then smelted at 1520-1550℃ for 5-10 minutes. Inoculation: Molten iron B was inoculated with a silicon-strontium inoculant to obtain the target composition, the specific target composition is shown in Table 1; The molten iron was centrifugally cast and then air-cooled after demolding to obtain alloy cast iron cylinder liners. The corrosion loss rate and metallographic structure of the obtained cylinder liners were tested, and the results are shown in Table 1.

[0022] Table 1 Target composition and properties of alloy cast iron cylinder liners in Examples 1-20 Example 1 / 0.3 0.6 14.681 normal Example 2 / 0.6 0.6 9.556 normal Example 3 / 0.8 0.6 9.353 normal Example 4 / 1.5 0.6 3.342 normal Example 5 / 0.3 0.7 4.684 normal Example 6 / 0.6 0.7 0.348 normal Example 7 / 0.8 0.7 0.342 normal Example 8 / 1.5 0.7 0.165 Hardness greater than 330HB, difficult to process Example 9 / 0.3 0.9 0.352 normal Example 10 / 0.6 0.9 0.334 normal Example 11 / 0.63 0.71 0.329 normal Example 12 / 0.68 0.79 0.328 normal Example 13 / 0.72 0.83 0.319 normal Example 14 / 0.76 0.88 0.315 normal Example 15 / 0.8 0.9 0.287 Excessive cementite content necessitates scrapping. Example 16 / 1.5 0.9 0.197 Excessive cementite content necessitates scrapping. Example 17 / 0.3 1.0 0.325 Excessive cementite content necessitates scrapping. Example 18 / 0.6 1.0 0.302 Excessive cementite content necessitates scrapping. Example 19 / 0.8 1.0 0.287 Excessive cementite content necessitates scrapping. Example 20 / 1.5 1.0 0.193 Excessive cementite content necessitates scrapping. As can be seen from the test results in the table above, in Example 14, when the Cr content in the casting is 0.76% and the Sn content is 0.88%, the corrosion resistance rate of the casting is 0.315%, achieving the optimal corrosion resistance state, while also exhibiting excellent machinability. When the Cr content is less than 0.6% and the Sn content is less than 0.7%, the material has a certain corrosion resistance, but this is not the optimal value. When the Cr content is greater than 1.0%, the casting hardness is greater than 330 HB, making it difficult to machine. When the Sn content is greater than 0.9%, the casting contains cementite, resulting in a substandard metallographic structure and rendering it unusable.

[0023] Comparative Example 1 A common type of cylinder liner alloy cast iron used in production has the following chemical composition: C: 3.0 wt%, Si: 2.0 wt%, Mn: 0.5 wt%, S: 0.03 wt%, P: 0.2 wt%. The preparation method is similar to that of the embodiments of this invention. This cast iron has a tensile strength of up to 260 MPa and a hardness of 220 HB. Accelerated corrosion tests under simulated working conditions were conducted according to the standard test for the cylinder liner of Comparative Example 1, according to GB / T 2100-2017 "General Corrosion-Resistant Steel Castings". Formic acid corrosion tests were performed at a concentration of 5% formic acid at a constant temperature of 40℃, and the corrosion loss rate was 6.120%.

[0024] Comparative Example 2 A high-strength aluminum-nickel-copper alloy gray cast iron has the following chemical composition: C: 3.2 wt%, S: 0.10 wt%, Si: 2.5 wt%, P: 0.25 wt%, Mn: 0.8 wt%, Cu: 0.5 wt%, Al: 2.7 wt%, Ni: 0.5 wt%, Sn: 0.6 wt%. The preparation method is similar to that of the embodiments of this invention. This cast iron has a tensile strength of up to 290 MPa and a hardness of 260 HB. Accelerated corrosion tests under simulated working conditions were conducted according to the standard test for cylinder liners in Comparative Example 2, according to GB / T 2100-2017 "General Corrosion-Resistant Steel Castings". Formic acid corrosion tests were performed at a concentration of 5% at a constant temperature of 40℃, and the corrosion loss rate was 5.443%.

[0025] Comparative Example 3 A copper-boron-molybdenum alloy gray cast iron has the following chemical composition: C 3.4wt%, S: 0.10wt%, Si: 2.4wt%, P: 0.25wt%, Mn: 0.8wt%, Cr: 0.4wt%, Cu: 1.7wt%, B: 0.07wt%. The preparation method is similar to that of the embodiments of this invention. The tensile strength of this cast iron is not less than 290MPa, and the hardness is 264HB. According to GB / T 2100-2017 "General Corrosion-Resistant Steel Castings," a simulated accelerated corrosion test was conducted on the cylinder liner of Comparative Example 3, and a formic acid corrosion test was performed. With a formic acid concentration of 5%, the corrosion loss rate was 12.668% under a constant temperature environment of 40℃.

[0026] The preferred embodiments of the present invention have been described in detail above. However, it should be understood that the above description is for illustrative purposes only and does not constitute any limitation on the scope of the present invention. Those skilled in the art can make substitutions or changes to certain features of the present invention without departing from the spirit and scope of the invention, and such substitutions or changes should be considered to fall within the protection scope of the claims of the present invention.

Claims

1. A corrosion-resistant alloy cast iron cylinder liner, characterized in that, It is composed of the following components: 2.5~3.1wt% C, 1.4~2.5wt% Si, 0.5~1.2wt% Mn, 0.1~0.4wt% P, 0.02~0.12wt% S, 0.3~1.5wt% Cr, 0.5~1.5wt% Cu, 0.6~1.0wt% Sn, and the balance is Fe.

2. The corrosion-resistant alloy cast iron cylinder liner according to claim 1, characterized in that: It is composed of the following components: 3.0~3.1wt% C, 1.9~2.1wt% Si, 0.75~0.85wt% Mn, 0.2~0.3wt% P, 0.04~0.06wt% S, 0.6~0.8wt% Cr, 0.6~0.7wt% Cu, 0.7~0.9wt% Sn, and the balance is Fe.

3. The method for preparing a corrosion-resistant alloy cast iron cylinder liner as described in claim 1, characterized in that, The following smelting steps are included: Smelting: Add No. 18 pig iron, scrap steel, and carbon recarburizer with 98% carbon content to a 3t medium-frequency electric furnace for smelting, including 1500Kg of pig iron, 1350Kg of scrap steel, and 45Kg of carbon recarburizer; The pig iron is added in three batches of 500, 500, and 500 kg, and the scrap steel is added in three batches of 450, 450, and 450 kg. The carbon raiser is added at once in batches of 45 kg. The feeding process is carried out in batches and continuously. During this process, the smelting power is controlled at 80% of the total power. When the materials in the furnace are completely melted and the liquid surface at the furnace mouth is visible, the power is increased to 100%. The molten iron is boiled at high temperature for 5-10 minutes at 100% power. A slag remover is added to the surface of the molten iron to remove slag until the liquid surface is clean. The smelting temperature is 1520-1550℃ to obtain molten iron A. Tempering: Add an alloy to molten iron A for tempering. The required weight of the alloy is calculated based on the difference between the original molten iron A and the target value of molten iron B. After adding the alloy, spectral detection is used to finally obtain molten iron B. After adding the alloy, smelt at a temperature of 1520-1550℃ for 5-10 minutes. Inoculation: Molten iron B is inoculated with a silicon-strontium inoculant to obtain a composition of 2.5-3.1 wt% C, 1.4-2.5 wt% Si, 0.5-1.2 wt% Mn, 0.1-0.4 wt% P, 0.02-0.12 wt% S, 0.3-1.5 wt% Cr, 0.5-1.5 wt% Cu, 0.6-1.0 wt% Sn, with the balance being Fe; The molten iron after inoculation is poured through centrifugal casting, and after being removed from the mold, it is air-cooled to obtain alloy cast iron cylinder liners.

4. The method for preparing the corrosion-resistant alloy cast iron cylinder liner according to claim 3, characterized in that: The composition obtained by inoculation is: 3.0~3.1wt% C, 1.9~2.1wt% Si, 0.75~0.85wt% Mn, 0.2~0.3wt% P, 0.04~0.06wt% S, 0.6~0.8wt% Cr, 0.6~0.7wt% Cu, 0.7~0.9wt% Sn, with the balance being Fe.

5. The method for preparing the corrosion-resistant alloy cast iron cylinder liner according to claim 3, characterized in that: The pouring temperature of the centrifugal casting is controlled at 1350~1390℃, and the exit temperature is 700-800℃.

6. The method for preparing the corrosion-resistant alloy cast iron cylinder liner according to claim 3, characterized in that: The air cooling process is as follows: air cool with the metal mold for 30 seconds, water cool with the metal mold for 240 seconds, then air cool with the metal mold for 120 seconds, until the blank cavity reaches 700-800℃, then remove from the mold and air cool to the natural temperature.